The Axiological Dimension Of Emotional Development In Modern Education - Alliyarov, Ashraf (Equilibrium: Jurnal Pendidikan, 2026)
This study explores the pedagogical potential of the axiological approach in developing students’ emotional intelligence within contemporary educational environments. The relevance of the research is обусловлена the growing need to humanize education and to integrate value-based learning with students’ emotional and social development. The purpose of the study is to substantiate the theoretical and methodological foundations of the emotional–value approach and to determine its effectiveness in fostering emotional awareness, self-regulation, empathy, and value-oriented behavior among students.mThe research methodology includes theoretical analysis, comparative synthesis, and interpretative review of contemporary pedagogical and psychological literature on emotional intelligence and value-based education. The findings demonstrate that the integration of axiological principles into the educational process significantly enhances students’ emotional competence by linking cognitive learning with moral values and personal meaning. Value-oriented pedagogical environments promote reflective thinking, emotional responsibility, and socially constructive behavior. The study concludes that the effective development of emotional intelligence requires a holistic value-centered pedagogical framework. The axiological approach serves as a productive methodological basis for harmonizing emotional, cognitive, and moral dimensions of student development in modern education.